Comparative Study of Pharmaceutical, Herbal Medicine, and Low-Value Alternating Electromagnetic Radiation as Anti-Malaria Treatment - Abayomi Alade (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2023)
Malaria is a significant global health burden, particularly in regions with limited healthcare resources. Pharmaceutical interventions, specifically artemisinin-based combination therapies (ACTs), have long been the mainstay of malaria treatment due to their proven efficacy in eliminating Plasmodium parasites. Herbal medicine has also gained attention as a potential alternative or adjunctive therapy. Nevertheless, the emergence of drug-resistant strains, notably in Southeast Asia and Africa, poses a considerable challenge to the effectiveness of these pharmaceutical treatments. Using low-value alternating electromagnetic field (EMF) radiation as an anti-malaria treatment is a novel approach that requires further investigation to determine its therapeutic potential. This research studies the comparative analysis of the effect of pharmaceutical intervention, herbal medicine, and low-value alternating EMF as anti-malaria treatments. The research methodology involves a systematic literature review of relevant scientific databases, design, construction, and administration of 20mT & 30mT electromagnetic field, Lumartem and Thitonia Diversifolia (Jume 12) to plasmodium berghei-infected mice for four days consecutively at the same time interval. Results revealed that all treatments were significantly effective. Lumartem is maximally effective from the third day, while Tihonia Diversifolia was maximally effective on the second day. EMF 10mT was maximally effective on the third day, while EMF 20mT did not fully align with the non-infected mice trend, but it is likely to align if treatment continues. The results of this comparative study will contribute to the body of knowledge regarding the effectiveness of pharmaceutical, herbal medicine, and low-value alternating electromagnetic field treatments for malaria.